Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1590/s1808-86942009000500011
|View full text |Cite
|
Sign up to set email alerts
|

Futura study: evaluation of efficacy and safety of rupatadine fumarate in the treatment of persistent allergic rhinitis

Abstract: Al lergic rhinitis affects 10-30% of the population, negatively impacting one's quality of life and productivity. It has been associated with sinusitis, otitis media, sleep disorders, and asthma. Rupatadine is a second generation antihistamine with increased affinity to histamine receptor H1; it is also a potent PAF (platelet-activating factor) antagonist. It starts acting quite quickly, offers long lasting effect, and reduces the chronic effects of rhinitis. Aim: this study aims to assess the efficacy and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
4
9
1
Order By: Relevance
“…We did not find any significant change in biochemical parameters with either drug. This observation supports the findings of a previous study on the safety of rupatadine …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We did not find any significant change in biochemical parameters with either drug. This observation supports the findings of a previous study on the safety of rupatadine …”
Section: Discussionsupporting
confidence: 93%
“…Thus, this increase in the incidence of adverse events may be attributable to the more thorough reporting of adverse events in comparison with that in studies in which patients have reported adverse events spontaneously. We found no changes in ECG, in line with previous studies that have reported similar ECG findings …”
Section: Discussionsupporting
confidence: 93%
“…This observation supports the previous study of analysis of rupatadine and olopatadine. [26] There was no significant difference in differential monocyte count and differential basophil count in both groups. In our study, we did not find any significant change in biochemical parameters.…”
Section: Discussionmentioning
confidence: 94%
“…[6] Another comparative dose ranging trial of rupatadine showed improvement in nasal and ocular symptoms of AR. [10] Our study supports this finding of a significant reduction in symptom score and improvement in nasal symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation